PROFESSIONAL LIABILITY INSURANCE IN UZBEKISTAN - Sh. F. Kobilzhonova (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The activities of entrepreneurs are constantly exposed to all kinds of risks. Possible emergencies, natural disasters, and theft of an entrepreneur’s property can cause him material losses. Insurance will help an entrepreneur to make up for such losses. This article provides information on documentation that allows you to judge the causes, course and consequences of the error, the nature and extent of the damage caused. Provide all possible assistance to the Insurer in judicial and out-of-court protection in case of claims for damages for an insured event.